North American Buddhists in social context - Numrich, Paul David, 1952- (Religion and the Social Order, 2008)
This volume marks an important milestone in the growing literature on North American Buddhists-the first multi-author collection of social scientific scholarship on the topic. Chapters examine the current state of research and key aspects of Buddhist life and experience in social context, including group identity and status, religious practices, organizational structures, generational dynamics, relations with non-Buddhist groups and the larger society, and migratory and adaptive processes. Case studies feature Southeast Asian, Japanese, Taiwanese, Korean, meditation-oriented, and socially engaged Buddhists. For social scientists, this volume provides a convenient overview of scholarship heretofore available only piecemeal. All readers will discover how social scientific perspectives and approaches helpfully inform the study of North American Buddhists.